RU SCHOLARS, SOCIAL NETWORKS, AND BUREAUCRACY: DONGHAI 東海 MEN AND MODELS FOR SUCCESS IN WESTERN HAN CHINA (206 b.c.e.–9 c.e.). (September 2019) - Cai, Liang
Abstract: In this study I take men from Donghai, a region of northeast China, as a case study for examining models of success in the Western Han (206b.c.e. –9c.e. ). Employing digital tools to mine data from The Grand Scribe's Records ( Shi ji ) and The History of the Western Han ( Han shu ), I explore the social networks and career patterns of men from a region that enjoyed a reputation for producing a remarkable number of high officials and celebrated Ru . I focus on three questions. First, what was the social mechanism that enabled people to distinguish themselves at both the local and the imperial levels? Second, did these celebrated men from Donghai serve as bridges connecting the local to the capital, directing resources back to their hometown and helping their local fellows achieve success? Third, did their positions in the central government remove them from local society by transforming them into capital-dwelling elites primarily concerned about the success of their families in the central court? In addressing these questions, I probe the dynamics between bureaucratic hierarchy, social networks, and the flow of talent and resources. I investigate various understandings of prestige and the strategies for climbing the ladder of success. Furthermore, I ask which forms of social prestige—for example, academic reputation, wealth, social networks—could bypass the hierarchical system imposed by the imperial bureaucracy, providing direct access to lofty positions. Did the patterns of success seen in the Donghai group reflect a bias built into the sources, constitute a regional variation, or provide a universal model for success in early imperial China? 提要: 西漢時期，數量可觀的高層官員和儒生來自東海郡。以他們為研究中心，本文旨在探討西漢儒生的成功模式（公元前 206 年—公元前 9 年）。 利用數字人文挖掘《史記》和《漢書》中人物傳記的數據，本文重現了來自東海地區官員和儒生的社交網絡和仕途模式。在本文中，我專注於三個問題。首先，什麼樣的社會機制能夠讓沒有顯赫家庭背景的人取得政治上的成功， 爬上權力的金字塔。 第二，這些來自東海的官員和儒生是否成爲連接當地與京城的橋樑，是否將資源引向家鄉，並幫助同籍貫的人取得成功？第三，東海官員在中央朝廷任職之後， 是否逐漸脫離了地方社會，而成爲以京城為中心的精英。通過回答這些問題，我探討了官僚等級制度，社交網絡，以及人才和資源流動之間的動態關係。本文研究了西漢時期各種對資源的理解以及攀登成功階梯的策略，探尋哪種形式的社會資源—學術聲譽，財富，社交網絡 –可以幫助西漢儒生跨越官僚等級制度，直接進入高層職位。最後本文討論了東海集團的成功模式是否僅僅反應了一個地區的特例，還是提供了早期帝國儒生成功的普遍模式？